2009
DOI: 10.1002/dmrr.944
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid‐mediated effects on metabolism are reversed by targeting 11 beta hydroxysteroid dehydrogenase type 1 in human skeletal muscle

Abstract: Targeted reduction or pharmacological inhibition of HSD1 in primary human skeletal muscle cells prevents the effects of cortisone, but not cortisol, on glucose metabolism and palmitate oxidation. Furthermore, the glucocorticoid-mediated reductions in glucose metabolism are dependent on PDK4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…The pre-receptor metabolism of the glucocorticoids determine the tissue specific sensitivity, which is also partly regulated by enzyme 11β-HSD1 that converts inactive cortisone to active cortisol (Salehzadeh et al, 2009). Increased adipose tissue 11β-HSD expression has been observed in obesity, which may lead to increased local glucocorticoid signaling (Stimson et al, 2009).…”
Section: Role Of 11βhsd1 In Glucocorticoid-mediated Effects On Skeletmentioning
confidence: 99%
“…The pre-receptor metabolism of the glucocorticoids determine the tissue specific sensitivity, which is also partly regulated by enzyme 11β-HSD1 that converts inactive cortisone to active cortisol (Salehzadeh et al, 2009). Increased adipose tissue 11β-HSD expression has been observed in obesity, which may lead to increased local glucocorticoid signaling (Stimson et al, 2009).…”
Section: Role Of 11βhsd1 In Glucocorticoid-mediated Effects On Skeletmentioning
confidence: 99%
“…The induction of PDK4 gene transcription by GR may contribute to GC-regulated glycogen metabolism in myotubes. One report shows that a reduction of the expression of PDK4 in human primary myotubes diminishes GC-repressed glycogen synthesis [143]. Notably, GC also inhibits insulin-stimulated glycogen synthesis and the activity of glycogen synthase [9].…”
Section: Glycogen Metabolismmentioning
confidence: 99%
“…Thus, the induction of Pdk4 plays a critical role in GC-decreased glucose utilization (Sugden and Holness, 2003). Recent studies indicated that, in human primary myotubes, GC–repressed glycogen synthesis is diminished with reduced expression of PDK4 (Salehzadeh et al, 2009). GCs upregulate Pdk4 gene transcription in both liver and skeletal muscle, and GREs of human PDK4 and rat Pdk4 have been identified (Connaughton et al, 2010; Kwon et al, 2004).…”
Section: The Regulation Of Glucose Metabolism By Glucocorticoidsmentioning
confidence: 99%